The forgotten trade : comprising the Log of the Daniel and Henry of 1700 and Accounts of the slave trade from the minor ports of England, 1698-1725 /: comprising the Log of the Daniel and Henry of 1700 and Accounts of the slave trade from the minor ports of England, 1698-1725. (2011) - Unknown
No abstract available